You can solve it using elimination as described by the student below. It's just as easy to solve using substitution. If you're using substituition, you first need to get a variable by itself. The easiest way to do this would be to add 4y to both sides in the first equation to get x = 4y + 1. Then you're going to "substitute" this in for x in the second equation. So instead of writing 3**x** + 4y = 7, you now have 3(4y + 1) = 7. Distribute the 3 and you get 12y + 3 = 7. Subtract 3 from both sides: 12y = 4. Divide both sides by 12 to solve for y. So y = 4/12 = 1/4.

Now to solve for x, you plug in 1/4 for y into one of the equations.

3x + 4(1/4) = 7

3x + 1 = 7 Subtract 1 from both sides.

3x = 6 Divide both sides by 3

x = 2

So your solution is x = 2, y = 1/4. This can also be written as an ordered pair: (2,1/4). Notice that the same answer is found no matter whether you use substitution or elimination.

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now